Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

chubbytots

  • 3 years ago

for x=2^3 , Y=2^-3 and z=3^-1 , write each expression in simplest form with positive exponents a. xy

  • This Question is Closed
  1. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    \[xy=2^3\times 2^{-3}=2^{3-3}=2^0=1\]

  2. chubbytots
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    b. \[\frac{ x }{ y }\] c. \[x^{2}\] d. \[\sqrt[10]{z}\] e. \[\left( x + y \right)^2\] f.xyz

  3. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    \[\frac{x}{y}=\frac{2^3}{2^{-3}}=2^{3+3}=2^6\]

  4. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    how many of these you got?

  5. chubbytots
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    4 left :)

  6. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    \[x^2=(2^3)^2=2^6\]

  7. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    \[\sqrt[10]{z}=\sqrt[10]{3^{-1}}=3^{-\frac{1}{10}}=\frac{1}{\sqrt[10]{3}}\]

  8. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    \[(x+y)^2=x^2+2xy+y^2=2^6+2+2^{-6}\]

  9. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    and since \(xy=1\) we have \(xyz=z=3^{-1}\)

  10. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy